GOLD MORTGAGE FINANCING SYARIAH ON BANK SYARIAH MANDIRI - Zurika, Henny (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
The objective of this study was to determine how the implementation procedures, assessment of gold pawn syariah and the contribution resulting from the gold pawn Bank Syariah Mandiri branch in Medan. The research method that I use in this paper is the descriptive method where researchers presented an analysis of the procedures for implementing the pledge of gold, gold pawn goods valuation method, advantages and disadvantages of the products and the contribution from the gold mortgage products on a standalone Islamic bank branch in Medan. It can be concluded procedures for implementing the pledge of gold syariah easy enough, prospective customers fill out a form and carry a pledge in the form of gold, assessment  is in  accordance with  the standard price  of gold  is  determined  by division Islamic business, its advantages and disadvantages relevant enough, the contribution resulting from product pawning gold syariah is a fee-based income increased in value income, fee based income generated is an advantage compared to other products. Keywords: Financing, Gold Pawn Syariah, and Islamic Bank